Pengaruh Kualitas Pelayanan, Religiusitas, dan Norma Subjektif Terhadap Kepatuhan WPOP pada KPP Pratama Tabanan - Karmanata, A.A. Gede Rai; Setiawan, Putu Ery (E-Jurnal Akuntansi; Vol 29 No 3 (2019), 2019)
This study aims to determine the effect of service quality, religiosity, and subjective norms on individual taxpayer compliance at the Tabanan Primary Tax Office. The sample in this study was obtained based on the calculation of the Slovin formula, so as to obtain as many as 100 samples of WPOP registered as Individual Taxpayers at the Tabanan Primary Tax Office. The analysis technique used in this study is multiple linear regression. The results of this study indicate that good service quality, strong religiosity, and high subjective norms significantly influence individual taxpayer compliance registered at the Tabanan Primary Tax Office. This research can be used as a motivation for the Tabanan Pratama Tax Office to be able to maintain good service quality for satisfaction and comfort of taxpayers to carry out their tax obligations. Keywords : Service Quality; Religiosity; Subjective Norms; WPOP Compliance.